2019
DOI: 10.1155/2019/1238581
|View full text |Cite
|
Sign up to set email alerts
|

GAS1Deficient Enhances UPR Activity inSaccharomyces cerevisiae

Abstract: Beta-1,3-glucanosyltransferase (Gas1p) plays important roles in cell wall biosynthesis and morphogenesis and has been implicated in DNA damage responses and cell cycle regulation in fungi. Yeast Gas1p has also been reported to participate in endoplasmic reticulum (ER) stress responses. However, the precise roles and molecular mechanisms through which Gas1p affects these responses have yet to be elucidated. In this study, we constructed GAS1-deficient (gas1Δ) and GAS1-overexpressing (GAS1 OE) yeast strains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In fact, the top marker gene for this cluster, growth arrest specific-1 (GAS1), is an anti-mitogenic factor that mediates the growth arrest of fibroblasts. The Saccharomyces cerevisiae homolog of GAS1 plays an important role in the endoplasmic reticulum stress response (Cui et al, 2019). Thus, the minor interstitial fibroblasts might play a role in upregulating pathways involved in protein homeostasis.…”
Section: Classification Of the Stromal Cellsmentioning
confidence: 99%
“…In fact, the top marker gene for this cluster, growth arrest specific-1 (GAS1), is an anti-mitogenic factor that mediates the growth arrest of fibroblasts. The Saccharomyces cerevisiae homolog of GAS1 plays an important role in the endoplasmic reticulum stress response (Cui et al, 2019). Thus, the minor interstitial fibroblasts might play a role in upregulating pathways involved in protein homeostasis.…”
Section: Classification Of the Stromal Cellsmentioning
confidence: 99%
“…In fact, growth arrest specific-1 ( GAS1 ) is an anti-mitogenic factor that mediates growth arrest of fibroblasts. The Saccharomyces cerevisiae homologue of GAS1 plays an important role in the endoplasmic reticulum stress response (Cui et al, 2019). Thus, this population of fibroblasts might play a role in upregulating pathways involved in protein homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…2000 ; Levin 2005 ). In addition to the established function in the cell wall, it was reported that GAS1 may play roles in several intracellular processes such as DNA damage response ( Eustice and Pillus 2014 ), locus-specific transcriptional silencing ( Koch and Pillus 2009 ), and ER stress response ( Cui et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…2003 ; Koch and Pillus 2009 ), it has been proposed that Gas1 is involved in post-translational glycosylation of putative chromatin components ( Koch and Pillus 2009 ; Eustice and Pillus 2014 ). Loss of GAS1 also elevates the unfolded protein response (UPR) and renders the mutant cells resistant to tunicamycin-induced ER proteotoxic stress ( Cui et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%